A Feasible Topology of DC Collection Valve for Long-Distance Offshore Wind Farms and Cost-Effective Analysis - Xiupu LIAO; Quan ZHOU; Lei LI; Binbin LI; Zhiyuan WANG; Ming YANG; Dianguo XU (Zhongguo dianli)
HVDC is a preferred technology for high-power and long-distance offshore wind farms, and the valve plays a pivotal role. Due to the high cost, large footprint and weight of valve, and high construction cost of offshore platform, an evolution is anticipated from traditional modular multilevel converter (MMC) based AC collection valve to the DC/DC transformer (DCT) based DC collection valve. Firstly, based on analyzing the technical characteristics and feasible topology of the DC collection valve, it is proposed to adopt the capacitive energy transmission (CET) principle based DCT, which presents low-cost, small footprint, light weight and low power loss. And then the topology of CET-DCT is improved into the bipolar topology for engineering applications, and the operation principle is also discussed. The effectiveness of the DC collection valve has been verified by simulation and experimental results, and the cost-effectiveness of the CET-DCT based DC valve is concluded by comparison with the MMC based AC collection valve.